Implementation of Digital Health in Addressing Global Threats: Lessons from the Use of Technology during COVID-19 Pandemic in Indonesia - Shifa, Naili; Tiasari, Anisa; Siregar, Kemal N (Kesmas, 2024)
This research conducted a systematic literature review to explore the implementation of digital health in Indonesia, focusing on the digital health policies, usage during the COVID-19 pandemic, benefits, and lessons learned. The study identified 10 relevant journals through database searches and analyzed the trends in publication, productive journals, and top institutions involved in digital health research. The findings revealed an increasing interest in digital health, with a growing number of published articles from 2021 to 2023. ScienceDirect emerged as the most productive journal, followed by PubMed and MDPI. The University of Indonesia and the University of Gajah Mada were the leading institutions in digital health research in Indonesia. The study discussed the implementation of digital health during the pandemic, highlighting its role in epidemic surveillance, telemedicine services, and data systems for COVID-19 management. The research also emphasized the challenges faced in the 3T regions (remote areas) of Indonesia due to limited internet access and infrastructure. Overall, the findings contribute to understanding the landscape of digital health in Indonesia and provide insights into its benefits and lessons learned.